MENAKAR KELAYAKAN EKONOMI DAN RISIKO PENDAPATAN USAHATANI PADI SAWAH DI DESA CANGKRINGSARI KECAMATAN SUKODONO KABUPATEN SIDOARJO - Anggraeni, Yuni Tiara; Soedarto, Teguh; Nurhadi, Eko (Jurnal Hutan Tropis, 2025)
This research endeavors to 1) Analyze the costs, revenues, profitability, and economic feasibility of rice farming 2) Analyze the degree of income risk in rice farming. The research site was chosen through a purposive method. The researchers employed quantitative methods with a descriptive framework to conduct the study. The research sample consisted of 38 rice farmers selected using probability sampling. The results showed that the average land area of farmers was 0.36 hectares. The total cost during the rainy season reaches Rp2,957,031, while in the dry season it is Rp7,186,499. Revenue in the rainy season is Rp7,696,842, while in the dry season it reaches Rp10,017,000. Income in the rainy season is Rp4,739,811, and in the dry season it is Rp7,186,499. Economic feasibility is measured using several indicators. In the rainy season, the R/C Ratio is 2.41, the B/C Ratio is 1.41, the Production BEP is 462,036, and the BEP Price is Rp2,787. In the dry season, the same values are 3.33 for the R/C Ratio, 2.33 for the B/C Ratio, 404,357 for the Production BEP, and Rp2,281 for the BEP Price. Furthermore, we assess revenue risk utilizing the Coefficient of Variation (CV) in our research. In the rainy season, the KV value is 0.031, while in the dry season it is 0.026. In conclusion, the economy of rice farming in Cangkringsari Village is more profitable during the dry season than padpenga with the rainy season. In addition, the risk of income obtained is higher in the rainy season compared to the dry season.